Bilateral diffuse cystic renal dysplasia in a 9-day-old Thoroughbred filly - Medina-Torres, Carlos E. (Canadian Veterinary Medical Association, 2014)
A 9-day-old Thoroughbred filly was presented for diarrhea and lethargy. Diagnostic test results were compatible with severe renal dysfunction. Diffuse cystic lesions of both kidneys were identified on ultrasonographic examination. Postmortem examination confirmed the presence of multiple renal cysts. Congenital nephropathy compatible with bilateral diffuse cystic renal dysplasia was diagnosed.